Handbook of geotechnical investigation and design tables - Look, Burt (CRC Press, 2014)
This practical handbook of properties for soils and rock contains in a concise tabular format the key issues relevant to geotechnical investigations, assessments and designs in common practice. There are brief notes on the application of the tables. These data tables are compiled for experienced geotechnical professionals who require a reference document to access key information. There is an extensive database of correlations for different applications. The book should provide a useful bridge between soil and rock mechanics theory and its application to practical engineering solutions.